Mitochondrial protein biogenesis in the synapse is supported by local translation. (18th June 2020) - Kuzniewska, Bozena; Cysewski, Dominik; Wasilewski, Michal; Sakowska, Paulina; Milek, Jacek; Kulinski, Tomasz M; Winiarski, Maciej; Kozielewicz, Pawel; Knapska, Ewelina; Dadlez, Michal; Chacinska, Agnieszka; Dziembowski, Andrzej; et al.
Abstract: Synapses are the regions of the neuron that enable the transmission and propagation of action potentials on the cost of high energy consumption and elevated demand for mitochondrial ATP production. The rapid changes in local energetic requirements at dendritic spines imply the role of mitochondria in the maintenance of their homeostasis. Using global proteomic analysis supported with complementary experimental approaches, we show that an essential pool of mitochondrial proteins is locally produced at the synapse indicating that mitochondrial protein biogenesis takes place locally to maintain functional mitochondria in axons and dendrites. Furthermore, we show that stimulation of synaptoneurosomes induces the local synthesis of mitochondrial proteins that are transported to the mitochondria and incorporated into the protein supercomplexes of the respiratory chain. Importantly, in a mouse model of fragile X syndrome, Fmr1 KO mice, a common disease associated with dysregulation of synaptic protein synthesis, we observed altered morphology and respiration rates of synaptic mitochondria. That indicates that the local production of mitochondrial proteins plays an essential role in synaptic functions. Synopsis: Using global proteomic analysis and a mouse model of fragile X syndrome, Fmr1 KO mice, this study reveals that the local production of mitochondrial proteins plays an essential role in synaptic functions. Mitochondrial proteins represent a large pool of proteins synthesized locally at the synapse. Newly synthesized mitochondrial proteins are imported into the mitochondria and incorporated into the respiratory chain complexes. Uncoupling of mitochondria and blocking mitochondrial import inhibits incorporation of de novo synthesized proteins into the mitochondrial protein complexes. In the mouse model of fragile X syndrome, in which synaptic translation is dysregulated, the physiology of mitochondria is altered. Abstract : Using global proteomic analysis and a mouse model of fragile X syndrome, Fmr1 KO mice, this study reveals that the local production of mitochondrial proteins plays an essential role in synaptic functions.